Evaluasi Layanan Referensi di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Husna, Hanisatul; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
The purpose of writing this article is to describe: 1) evaluation of reference services; (2) determine the obstacles encountered in implementing the evaluation of reference services; and (3) determine the efforts to overcome obstacles encountered in the evaluation of reference services at Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat. Data collected by observation and interviews with librarians and user library in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat. Data analysis was done descriptive. Based on the results of the research, concluded as follows: (1) evaluation conducted by the reference services of Library and Archives routine yet, so there are still shortcomings in service; (2) there are still obstacles encountered in implementing the evaluation of reference services, so that the service provided is not maximized; and (3) efforts to be made by Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat in overcoming these obstacles. Keywords: Evaluation, services and references